Концептуальні положення управління поведінкою економічних агентів у цифровому просторі з використанням інструментів штучного інтелекту - Турлакова, С. С.; Turlakova, S. S. (Київський національний економічний університет імені Вадима Гетьмана, 2022)
Обґрунтовано актуальність дослідження механізмів взаємодії економічних агентів у цифровому просторі в межах поведінкової економіки. Запропоновано концептуальні положення, що визначають ключові параметри управління поведінкою економічних агентів у цифровому просторі з використанням інструмен-тів штучного інтелекту (ШІ) в межах їх рефлексивних характеристик, що визначають особливості їх поведінки. Концептуальні положення управління поведінкою економічних агентів у цифровому просторі передбачають дослідження впливу і визначення можливостей та загроз використання інструментів ШІ у процесі діагностики та управління поведінкою економічних агентів у цифро-вому просторі на макро- та мікрорівнях для зменшення ризиків «цифрового капіталізму» та забезпечити отримання загального позитивного соціально-економічного ефекту використання цифро-вого простору в межах поведінкової економіки.

The relevance of the study of the mechanisms of in-teraction of economic agents in the digital space within the limits of behavioral economics is substantiated. Conceptual provisions defining the key parameters of managing the behavior of economic agents in the digital space with the use of artificial intelligence tools within the reflexive characteristics of agents, which determine the peculiarities of their behavior, are proposed. The implementation of relevant concep-tual provisions will allow diagnosing the behavior of economic agents and identifying potential agents оf management in the digital space in accordance with the goals of socio-economic systems. The proposed concept is aimed at the use of existing open automated systems of ar-tificial intelligence, if the information is in open or specialized digital databases, and directed questionnaires with appropriate processing of the obtained results using tools of fuzzy logic and neural network modeling, if the information needs to be collected. In turn, manage-ment of the behavior of economic agents in the digital space using methods of information and reflexive influence and tools of artificial in-telligence will allow to increase the efficiency of achieving the specified goals of socio-economic systems according to the directions of use. Study of the influence and determination of opportunities and threats of using artificial intelligence tools for analysis and management of the behavior of economic agents in the digital space at macro- and micro- levels will reduce the risks of "digital capitalism" and ensure the overall positive socio-economic effect of using the digital space. Prospective directions of research regarding the development of methods and models of the proposed conceptual provisions are outlined.
Conceptual provisions of management of the behavior of economic agents in the digital space using artificial intelligence tools
Keywords: поведінкова економіка; «цифровий капіталізм»; управління поведінкою; економічний агент; інструменти штучного інтелекту; соціально-економічна система; behavioral economics; «digital capitalism»; behavior management; economic agent; artificial intelligence tools; socio-economic system